The burden of disease in Maputo City, Mozambique: registered and autopsied deaths in 1994 - Dgedge Martinho; Novoa Ana; Macassa Gloria; Sacarlal Jahit; Black James; Michaud Catherine; Cliff Julie (The World Health Organization, 2001)
OBJECTIVE: To classify the causes of death in Maputo City, Mozambique, using the methods of the Global Burden of Disease study, in order to provide information for health policy-makers and to obtain a baseline for future studies in Maputo City and provincial capitals. METHODS: Data were taken from the Maputo City death register and autopsy records for 1994. FINDINGS: A total of 9011 deaths were recorded in the death register, representing a coverage of approximately 86%. Of these, 8114 deaths (92%) were classified by cause. Communicable, maternal, perinatal, and nutritional disorders accounted for 5319 deaths; noncommunicable diseases for 1834; and injuries for 961. The 10 leading causes of registered deaths were perinatal disorders (1643 deaths); malaria (928); diarrhoeal diseases (814); tuberculosis (456); lower respiratory infections (416); road-traffic accidents (371); anaemia (269); cerebrovascular diseases (269); homicide (188); and bacterial meningitis (178). CONCLUSIONS: Infectious diseases of all types, injuries, and cerebrovascular disease ranked as leading causes of death, according to both the autopsy records and the city death register. AIDS-related deaths were underreported. With HIV infection increasing rapidly, AIDS will add to the already high burden of infectious diseases and premature mortality in Maputo City. The results of the study indicate that cause of death is a useful outcome indicator for disease control programmes.